THE COMPLEMENTARY RELATIONSHIP BETWEEN FINANCIAL CULTURE AND FINANCIAL LITERACY - AN APPLIED STUDY IN INSURANCE COMPANIES OPERATING IN THE IRAQ STOCK EXCHANGE (World Bulletin of Management and Law, 2023)
The current research aims to study the complementary relationship between financial culture in its dimensions (a culture of saving, a culture of spending, a culture of entrepreneurial ideas) and financial literacy in its dimensions (financial knowledge, financial behavior, financial attitudes), as the research was applied in a selected sample of insurance companies operating in the market Iraq Stock Exchange, and a set of statistical tools and programs were used to analyze and measure the correlation and influence relationships between the research indicators, which is a method)kurtosis&skewness(,)Amos.v.22(,)Spssv.22(The research reached a number of results, the most prominent of which was the existence of statistically significant correlation and influence relationships between financial literacy and financial literacy.
Keywords: Financial culture; financial literacy; Insurance companies